Stereoscopic analysis of polluted air masses - Sadeh, Willy Z., author; Fluid Dynamics and Diffusion Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1973)
Air pollution levels depend strongly upon the spatial and time variations of various pollutant concentrations. In the vicinity of pollution sources locally high concentrations and significant variation with time of pollutants occur. Surveillance of pollutant concentrations and dispersion requires adequate monitoring over large relevant areas at fixed time intervals. Particularly, strong and stable temperature inversion can cause such circulation conditions where vertical mixing of pollutants is prohibited. Remote sensing by means of stereo images obtained from flown cameras and scanners provides the potential to monitor the dynamics of pollutant mixing over large areas. Moreover, stereo technology permits efficient monitoring of pollutant concentration and mixing with sufficient detail. Consequently, regional standards on air quality can be set forth. Furthermore, methods to detect unpredicted and significant pollution variations can be developed. A method of remote sensing using stereo images is described. Preliminary results based on comparison with ground measurements by alternate method, e.g., remote hot-wire anemometer technique, are supporting the feasibility of stereo analysis using aerial cameras.
CER72-73WZS31.
May 1973.
Prepared for Aerospace Environment Division, George C. Marshall Space Flight Center, National Aeronautics and Space Administration, Contract No. NAS8-25236.
Keywords: Air -- Pollution -- Measurement; Air -- Pollution -- Analysis; Remote sensing